Therapeutic potential of rutin in premenstrual depression: evidence from in vivo and in vitro studies - Wang, Xiangjun; Xia, Xiaowen; Song, Xianliang; Zhou, Yi; Ma, Mingyu; Ren, Yashuang; Chen, Xitai; Xia, Zenghui; Guo, Yinghui; Song, Chunhong (Frontiers in Pharmacology, 2025)
IntroductionPremenstrual dysphoric disorder (PMDD) is a cyclical mood disorder that severely affects the daily life of women of reproductive age. Most of the medications being used clinically have limitations such as low efficacy, side effects, and high cost, so there is an urgent need to discover safer and more effective medications. Rutin is a natural flavonol glycoside with various pharmacological properties including antidepressant. The study of the efficacy and mechanism of action of rutin in PMDD-depressed subtype model rats plays an important role in the discovery of new drugs for the treatment of PMDD.MethodsBinding of rutin to gamma-aminobutyric acid type A receptors (GABAA receptors) was probed using molecular docking, microscale thermophoresis, radioactive receptor ligand binding assay and cell membrane clamp experiment. Behavioral tests in mice were performed to screen the optimal dose of rutin. Behavioral tests were performed to evaluate the effects of rutin on depressed mood, memory impairment, and social impairment in PMDD-depressed subtype model rats. HE staining and Golgi staining were performed to observe the neuronal damage in rat hippocampus. UHPLC-MS/MS targeted metabolomics was performed to detect the changes of neurotransmitter content in rat hippocampus. PCR array to detect the effect of rutin on mRNA expression of GABAA receptor partial subunits in rat hippocampus.ResultsThe docking score of rutin with the GABAA receptor benzodiazepine site was −11.442 and the gliding score was −11.470. The Kd of rutin with the GABAA receptor (α1β2γ2) was 1.17 ± 0.89 μM. Rutin competed with [H3]-flunitrazepam for the GABAA receptor benzodiazepine site and inhibited the inward flow of chloride ions (P < 0.05). In PMDD-depressed subtype rats, rutin alleviated depressed mood, memory impairment and social impairment, ameliorated hippocampal neuronal damage and reduces gamma-aminobutyric acid (GABA) and acetylcholine (ACh) levels (P < 0.05). Moreover, we found that rutin did not affect the relative mRNA expression of GABAA receptor subunits in rat hippocampus.DiscussionOverall, rutin alleviated depressed mood, memory impairment and social impairment in PMDD-depressed subtype rats, which may be related to binding to GABAA receptor benzodiazepine sites, inhibiting chloride ions inward flow, ameliorating hippocampal neuronal damage and reducing GABA and ACh levels. The results of this study provide an experimental basis and scientific evidence for the development of new drugs for the treatment of PMDD.